Treatment of Postherpetic Neuralgia With Intravenous Administration of Zinc Sulfate: A Case Report. Issue 1 (1st July 2018) - Lin, Yao-Tsung; Lan, Kuo-Mao; Wang, Li-Kai; Chen, Jen-Yin
Abstract : Gabapentinoids (gabapentin and pregabalin) are first-line drugs for postherpetic neuralgia (PHN), but some PHN patients have inadequate therapeutic response. Zinc deficiency has been identified as a risk factor for PHN. Zinc can alleviate pain through binding to Ca(v)3.2 T-channels and N -methyl-D-aspartate receptors. Mechanisms of gabapentinoids on neuropathic pain include inhibiting N -methyl-D-aspartate receptors and calcium channels. The aforementioned findings provide a molecular pain-relieving basis for zinc supplements as an add-on therapy to pregabalin. We report 2 zinc-deficient PHN patients who received zinc sulfate intravenously as an add-on therapy to pregabalin and responded well.